A short note on strong local diagnosability property of exchanged hypercubes under the comparison model. Issue 1 (2nd January 2020) - Ren, Yunxia; Wang, Shiying
Abstract : The diagnosability of a multiprocessor system plays an important role. The system and an interconnection network have a underlying topology, which are usually presented by a graph. The exchanged hypercube E H ( s, t ) has some good properties. In this paper, we study the diagnosis on E H ( s, t ) under the comparison model. Following the concept of the local diagnosability, the strong local diagnosability property is discussed. This property describes the equivalence of the local diagnosability of a node and its degree. We prove that E H ( s, t ) ( 2 ≤ s ≤ t and s =1, t =2) has this property under the comparison model. GRAPHICAL ABSTRACT: